2015
DOI: 10.1371/journal.pone.0127307
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT Study of Rhynchonkos stovalli (Lepospondyli, Recumbirostra), with Description of Two New Genera

Abstract: The Early Permian recumbirostran lepospondyl Rhynchonkos stovalli has been identified as a possible close relative of caecilians due to general similarities in skull shape as well as similar robustness of the braincase, a hypothesis that implies the polyphyly of extant lissamphibians. In order to better assess this phylogenetic hypothesis, we studied the morphology of the holotype and three specimens previously attributed to R. stovalli. With the use of micro-computed x-ray tomography (μCT) we are able to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(118 citation statements)
references
References 38 publications
5
110
1
2
Order By: Relevance
“…2 and 3). This contrasts with some prior studies that inferred a close relationship between caecilians and amniote-like lepospondyls (6) on the likely basis of convergent fossorial specializations (4,(36)(37)(38) or a close relationship between caecilians and batrachians to the exclusion of some Paleozoic total group lissamphibians on the basis of small size and reduced exoskeleton. In contrast to these prior hypotheses, the relationship between caecilians, Chinlestegophis, and stereospondyls is supported by numerous highly specific fusions or reductions of elements before the accomplishment of small body size or fossorial habitus as well as other highly specific features of overall cranial organization.…”
Section: Significancecontrasting
confidence: 98%
See 1 more Smart Citation
“…2 and 3). This contrasts with some prior studies that inferred a close relationship between caecilians and amniote-like lepospondyls (6) on the likely basis of convergent fossorial specializations (4,(36)(37)(38) or a close relationship between caecilians and batrachians to the exclusion of some Paleozoic total group lissamphibians on the basis of small size and reduced exoskeleton. In contrast to these prior hypotheses, the relationship between caecilians, Chinlestegophis, and stereospondyls is supported by numerous highly specific fusions or reductions of elements before the accomplishment of small body size or fossorial habitus as well as other highly specific features of overall cranial organization.…”
Section: Significancecontrasting
confidence: 98%
“…The former hypothesis, which proposes a polyphyletic Lissamphibia, is supported by general similarities in the gestalt of caecilians and the recumbirostran Rhynchonkos or the elongate lysorophian Brachydectes (40,41). However, recent studies of lepospondyl and caecilian braincases have found that much of this similarity has been overstated, and resemblances between the two groups may be due to miniaturization and shared fossorial lifestyle rather than common descent (36)(37)(38)42). Prior placement of caecilians within dissorophoids is due to a combination of strong phylogenetic support for a dissorophoid origin of batrachians (6) in combination with soft tissue support for a monophyletic Lissamphibia (5).…”
Section: Discussionmentioning
confidence: 99%
“…Ossification of the columella ethmoidalis fills the entire space between the olfactory nerve foramina in the largest specimen studied (Fig 7) but is restricted to the areas surrounding the olfactory nerves in smaller specimens (Figs 5 and 6) and absent entirely in the smallest specimens. Otherwise, the presphenoid is dorsoventrally flattened along its length and does not form an interorbital septum, in contrast with the condition seen in brachystelechids [41, 43] but consistent with the morphology seen in a number of other recumbirostrans [33, 42, 71]. A presphenoid has previously been described in Carrolla craddocki as the sphenethmoid [41] and appears to be present in a variety of other microsaurs as well [42, 43].…”
Section: Descriptionmentioning
confidence: 74%
“…Furthermore, some taxa not traditionally considered amniotes have appeared within the Amniota in some recent analyses. Most notably, the Recumbirostra, a group of small fossorial tetrapods traditionally classified within a larger order Microsauria and sometimes considered to be related to extant amphibians (Vallin and Laurin, 2004;Laurin, 2013, 2019), has recently been placed on the reptile stem based on neurocranial similarities (Pardo et al, 2015(Pardo et al, , 2017bSzostakiwskyj et al, 2015). This clade is relatively diverse in the Joggins Formation (Carroll, 1966;Mann et al, 2020), including forms such as Steenerpeton sylvae, Trachystegos megalodon, and Leiocephalikon problematicum, and Hylerpeton dawsoni, all of which can be confidently assigned to recumbirostran subclades for which complete articulated fossils exist.…”
Section: Phylogenetic Context Of the Amniote Crownmentioning
confidence: 99%
“…It increasingly appears that the former is not a settled feature of early tetrapod phylogeny. Recent redescription of a number of recumbirostrans, a clade of lepospondyls part of the previously recognized Order Microsauria (Carroll and Gaskill, 1978), has shown surprisingly reptile-like morphology of the braincase, suspensorium, and lower jaw (Pardo et al, 2015;Szostakiwskyj et al, 2015;Pardo and Anderson, 2016). In contrast, microcomputed tomography study of the aïstopod Lethiscus stocki, the earliest lepospondyl, has revealed extremely fishlike organization of the head (Pardo et al, 2017a), suggesting that the diverse morphology of lepospondyls may be a function of polyphyletic origins across the early tetrapod tree rather than a single adaptive radiation.…”
Section: Phylogenetic Context Of the Tetrapod Crownmentioning
confidence: 99%